User-reported quality of care: findings from the first round of the People's Voice Survey in 14 countries - Todd P Lewis, PhD; Munir Kassa, MD; Neena R Kapoor, MSc; Catherine Arsenault, PhD; Rodrigo Bazua-Lobato, MD; Rashmi Dayalu, MPH; Günther Fink, PhD; Theodros Getachew, PhD; Prashant Jarhyan, PhD; Hwa-Young Lee, PhD; Agustina Mazzoni, MD; Jesus Medina-Ranilla, MD; et al. (The Lancet Global Health, 2024)
Summary: High-quality care is essential for improving health outcomes, although many health systems struggle to maintain good quality. We use data from the People's Voice Survey—a nationally representative survey conducted in 14 high-income, middle-income, and low-income countries—to describe user-reported quality of most recent health care in the past 12 months. We described ratings for 14 measures of care competence, system competence, and user experience and assessed the relationship between visit quality factors and user recommendation of the facility. We disaggregated the data by high-need and underserved groups. The proportion of respondents rating their most recent visit as high quality ranged from 25% in Laos to 74% in the USA. The mean facility recommendation score was 7·7 out of 10. Individuals with high needs or who are underserved reported lower-quality services on average across countries. Countries with high health expenditure per capita tended to have better care ratings than countries with low health expenditure. Visit quality factors explained a high proportion of variation in facility recommendations relative to facility or demographic factors. These results show that user-reported quality is low but increases with high national health expenditure. Elevating care quality will require monitoring and improvements on multiple dimensions of care quality, especially in public systems.